STRATEGI PENGELOLAAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) DI LABORATORIUM KLINIK KOTA PEKANBARU - Fepi Yulianti; Yusni Ikhwan Siregar; Syahril Syahril (Jurnal Ilmu Lingkungan, 2019)
The number of work accidents in Indonesia tends to increase. There were 157.313 cases of work accidents during 2018. The laboratory is a workplace that has many potential hazards such as spills, chemical explosive reactions, punctured needles, exposure to infectious material. Workers in the laboratory are required to use the appropiate PPE, which is a lab coat, shoes, masks and gloves. Managers must provide proper PPE at work. Ineffective use, leads a problem that arises in the field. Management strategies for utilizing appropriate PPE usage are needed to improve the health status of workers. Percentage of clinical laboratory workers in Pekanbaru City (54,01%) and the availability of work guidelines in the form of SOP (65%), which classified as the quite good. The practice of PPE usege and the role of managers in managing, supplying, procuring and number of PPE is also classified as good category. Waste management in the laboratory uses a third party. Policy in the form of rewards (35%), administration of decrees/ sanctions (55%), availability of PPE signs / symbols (30%),  providing training to each officer (40%) and implementation health insurance in the form of MCU (50%) and vaccination (10%) is classified as poor category. Determination of management strategies for the use of PPE in the Pekanbaru clinical laboratory in this study using the SWOT calculation. The right strategy used from the results of the SWOT calculation is the survival strategy. The disadvantage is that there are no signs / symbols of PPE guidelines when entering the laboratory and the threat is that PPEwaste that has been used without being managed properly according to B3 waste regulations will contaminate the environment.